Reliability of second-order factor of a revised two-factor study process questionnaire (R-SPQ-2F) among university students in Malaysia - Wan Shahrazad bt Wan Sulaiman; Wan Rafaei Abdul Rahman; Mariam Adawiah Dzulkifli; Wan Samhanin Wan Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2013)
The approach students use during the learning process is important in determining the outcome they obtained from any learning activities. Two learning approaches using (SAL) learning theory, were identified namely surface and deep approaches. This study aimed to validate the Revised Two Factor Study Process Questionnaire (R-SPQ-2F). The R-SPQ-2F consists of 20 items with ten items measuring surface approach to learning and ten items measuring deep approach to learning. The sample consisted of 312 students from three public universities in Klang valley. These items were tested using reliability procedure and confirmatory factor analysis. Confirmatory factor analysis indicated a good fit with the hypothesized two-factor structure after elimination of six items. The final two-factor version of the questionnaire has good Cronbach alpha values and reasonable goodness-of-fit values of the hypothesized two-factor structure via second-order CFA. This validation process has resulted in a reliable and valid questionnaire which can be used to measure the learning approaches of university students.